The Role of the Board of Commissioners Gender Diversity on the Effect of Other Comprehensive Income on Audit Fees - Kurniawansyah, Deddy; Iswajuni, Iswajuni; Amalina, Dira Salwa (E-Jurnal Akuntansi; Vol 34 No 7 (2024), 2024)
Monitoring costs as agency costs can minimize information asymmetry  and improve the quality of the financial statement. The purpose of this  study was to examine the effect of other comprehensive income (OCI)  on audit fees, with the board commissioner's gender diversity  moderated. Non-Financial Company listed on the Indonesia Stock  Exchange from 2019 to 2023 represent the study's population. This  study sampling technique uses the census. The data analysis technique  uses PLS-SEM. This study found that OCI affects audit fees, and the  board of commissioners’s gender diversity strengthens that  relationship. The theoretical contribution of this study is to strengthen  agency theory in increasing agency costs to minimize conflicts of  interest and information asymmetry. For potential investors, as a  strategy to invest in companies that have high audit fees due to the strong encouragement from the board of commissioners’s gender diversity. For the government, strengthen the policy of female leadership on corporate boards to improve good governance. Keywords: Politic; Bonus; Earning Management; Real Activities